Reformasi Protestan : Pengaruh Martin Luther Terhadap Gereja an Dunia - Marlince Diana Lende; Junidar Gulo; Malik Bambangan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Protestant Reformation, initiated by Martin Luther in the 16th century, was a pivotal event in Christian history that shook the structure of the Catholic Church and had a profound impact on many aspects of life. This movement arose from dissatisfaction with church practices believed to be in conflict with Biblical teachings, such as the sale of indulgences. Through his 95 Theses, Luther emphasized that salvation could only be achieved through faith (sola fide) and that the Bible was the sole source of authority (sola scriptura). These teachings led to a split between the Catholic Church and Protestantism, sparking a broader theological reformation across Europe. Beyond its theological influence, the Protestant Reformation also brought about significant social, political, and cultural changes. Luther's teachings on the importance of education and literacy encouraged the translation of the Bible into local languages, allowing the faithful to access the Scriptures directly. The Reformation also introduced the concept of religious freedom and reshaped the relationship between church and state, with several countries adopting Protestantism as their official religion. Overall, the Protestant Reformation not only transformed the church's structure but also had a major impact on the development of Western social and political systems, creating new concepts of individual freedom and religious authority.